Quadrotor flight simulation in flightgear - Yue, Sai Kei. (2011)
In the recent years, there has been increasing interest in the development of the quadrotor for both military and civilian purposes due to its advantages which includes versatility and maneuverability in confined spaces. To optimise the design of a quadrotor model and preempt possible failures in actual flight, the use of flight simulation is important prior to actual flight. This project is focused on the flight simulation of a quadrotor in FlightGear. In addition to the study of the physics of the quadrotor, a greater understanding of the programming code behind FlightGear and the quadrotor model has been achieved. Improvements have been made to an existing quadrotor model. After the elimination of errors in the quadrotor's programming code, an autopilot which consists of a PID controller has been designed to enable the quadrotor model to perform autonomous stable flight in FlightGear. The iterative process of tuning the PID controller begins with the design of a data logging mechanism in FlightGear to aid the tuning process.